Effect of Plectranthus amboinicus Extract on BUN and Creatinine Levels and Cellular Response Proinflammatory Factors TNF-α and IL-1β on Gout Arthritis Patients - Lailatul Muniroh; Triska Susila Nindya; Santi Martini; Rondius Solfaine (Makara Journal of Health Research, 2014)
The purpose of this research was to develop anti-cytokine-based treatment using extract of Plectranthus amboinicus applied to gout arthritis (GA) patients. The research was quasi experimental, with a pretest-posttest randomized control group design. The samples were GA patientsin the Outpatient Installation of Internal Medicine in General Hospital Haji,Surabaya. The sample was comprised of 30 respondents. The respondents were divided into a treatment group and a control group. The treatment group was asked to take medicine from the hospital, coupled with Plectranthus amboinicus extract capsules, for 7 days, during which time patients' joint inflammation was observed. The control group was provided with only medication from the hospital, and their joint inflammation was likewise observed. Blood samples were taken before and after treatment, to measure the levels of blood urea nitrogen (BUN) and creatinine, as well as the concentrations of TNF-α; and IL-1β. There was a decrease in BUN and creatinine levels in the control group, but it was not significant, decreasing by 3% and 8%, respectively. The treatment group also showed elevated levels of BUN and creatinine, which also was not significant at 3% and 7%, respectively. There was a decrease in the concentration of TNF-α in the control group by 9% and 22%. The concentration of IL-1β in the control group increased by 18%, whereas,in the treatment group,it decreased by3%; however,the decreases in bothgroups were not significant.